Seasonal dynamics and spatial distribution of Dactylogyrus crucifer Wagener, 1857 on the gills of roach (Rutilus rutilus L.) from Lake Sapanca, Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2010)
This study determined the seasonal dynamics and spatial distribution of the monogenean parasite Dactylogyrus crucifer on the gills of roach Rutilus rutilus from Lake Sapanca, Turkey. A total of 183 specimens of roach between January and November 2005 were examined in monthly intervals. The highest mean intensity was recorded in March (227.1 +/- 87.14) and the lowest in November (13.3 +/- 8.2). Fifty three R. rutilus specimens were therefore investigated for spatial distribution of D. crucifer in March 2006. No significant differences in distribution were found according to any of the spatial determinants.
Keywords: Roach; monogenean; seasonal occurrence; spatial distribution; Lake Sapanca; PSEUDODACTYLOGYRUS-ANGUILLAE; MICROHABITAT DISTRIBUTION; PARASITES MONOGENEA; CENTRAL FINLAND; BINI MONOGENEA; EUROPEAN EEL; COEXISTENCE; FISH; COMMUNITIES; ECOLOGY